Summary of the Technical Specifications of the Geothermal Power Plants in the World: Revision 1. Report No. CATMEC/21 - DiPippo, R. (Brown University. Division of Engineering., 1978)
Worldwide geothermal power plant installed capacity is listed by country with year of startup. Tables containing technical data are given for each of the geothermal power units installed in the world and for some of those under construction or in planning. The data cover the primary mechanical areas of the power station including the turbine, condenser, gas extraction system, and heat extraction system. In the case of plants which are in the planning stage or under construction, the plant design specifications are listed but must be viewed as preliminary. (MHR)